2021
DOI: 10.1021/acs.iecr.0c04590
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine Interactions with Fe, Ni, Cr, and Stainless Steel Alloys

Abstract: The adsorption behavior of molecular iodine is important for understanding the spread of radioiodine in a nuclear accident. Prior experiments indicate that, in addition to the interaction with Fe, molecular iodine [i.e., I 2(g) ] also interacts with the next most abundant components of austenitic stainless steel (i.e., Ni, and Cr) at room temperature. In this study, we investigate iodine adsorption on Fe, Ni, and Cr while focusing on understanding the variables affecting adsorption as well as the iodine compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…However, Nb, Al, Ti, and Fe similar to Cu [13,16] strongly react with iodine under these conditions. Our results confirm the findings of Beck et al [38] that the reactiveness towards iodine decreases from Fe via Ni to Cr. In case of Al and Ti treated by these conditions, the chemical reaction products even cause brittleness of the surface and deterioration of the structural integrity of the material in the vicinity of the surface.…”
Section: Discussionsupporting
confidence: 93%
“…However, Nb, Al, Ti, and Fe similar to Cu [13,16] strongly react with iodine under these conditions. Our results confirm the findings of Beck et al [38] that the reactiveness towards iodine decreases from Fe via Ni to Cr. In case of Al and Ti treated by these conditions, the chemical reaction products even cause brittleness of the surface and deterioration of the structural integrity of the material in the vicinity of the surface.…”
Section: Discussionsupporting
confidence: 93%
“…It is also apparent from Figure 7b,c that the T m , so these types of parameters need to be considered. Regarding metal iodides, compounds like InI 3 are hygroscopic, where they can deliquesce in air and/or are highly water-soluble, 50,51 so they could have disadvantages regarding stability for long-term disposal in a repository. In a recent study, 52 it was shown that the relative humidity can also play a significant role in the reaction of metal substrates such as Ni 0 with I 2(g) , so this should also be considered for future sorbents.…”
Section: Discussionmentioning
confidence: 99%
“…Several different types of radioiodine sorbents have been reported for capturing iodine as a gas in different forms [e.g., I 2(g) and CH 3 I (g) ] or as an ion from liquid effluents (e.g., I – and IO 3 – ). The primary types of iodine capture systems include solid sorbents or liquid scrubber systems, often utilizing an aqueous hydroxide or molten hydroxide. ,, A wide range of solid sorbents have been reported that typically utilize active metal sites targeted to remove the iodine species from the environment through physisorption and/or chemisorption mechanisms. Some examples of solid sorbents include activated carbon; metal-exchanged zeolites like Ag-mordenite (Ag-MOR or AgZ), Ag-faujasite (Ag-FAU or AgX and AgY), and Ag-Linde type A (AgA); metal–organic frameworks; , metal-loaded aerogels or xerogels; , metal-impregnated ceramics; and solid metal substrates. , The current work will focus primarily on chemisorption-based iodine capture.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of solid sorbents include activated carbon; 7 metal-exchanged zeolites like Ag-mordenite (Ag-MOR or AgZ), Ag-faujasite (Ag-FAU or AgX and AgY), and Ag-Linde type A (AgA); 8−14 metal−organic frameworks; 15,16 metalloaded aerogels or xerogels; 17,18 metal-impregnated ceramics; 19 and solid metal substrates. 20,21 The current work will focus primarily on chemisorption-based iodine capture.…”
Section: Introductionmentioning
confidence: 99%